2013
DOI: 10.1080/17470919.2013.812536
|View full text |Cite
|
Sign up to set email alerts
|

Processing of subliminal facial expressions of emotion: A behavioral and fMRI study

Abstract: The recognition of emotional facial expressions is an important means to adjust behavior in social interactions. As facial expressions widely differ in their duration and degree of expressiveness, they often manifest with short and transient expressions below the level of awareness. In this combined behavioral and fMRI study, we aimed at examining whether or not consciously accessible (subliminal) emotional facial expressions influence empathic judgments and which brain activations are related to it. We hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 58 publications
3
38
1
1
Order By: Relevance
“…Although mood decline is likely to occur in response to mild stressors during sleep debt [42], sleep deprivation was reported to increase sensitivity to pleasurable experiences by lowering the threshold value in a task judging valence of pleasure-evoking pictures [43]. A change in nonconscious emotion processing can influence one’s conscious state, such as mood, feeling or emotional evaluation [44, 45]. Previous studies using nonconscious emotional stimuli have indicated that subjects can be unaware of their own emotional responses [11, 46].…”
Section: Discussionmentioning
confidence: 99%
“…Although mood decline is likely to occur in response to mild stressors during sleep debt [42], sleep deprivation was reported to increase sensitivity to pleasurable experiences by lowering the threshold value in a task judging valence of pleasure-evoking pictures [43]. A change in nonconscious emotion processing can influence one’s conscious state, such as mood, feeling or emotional evaluation [44, 45]. Previous studies using nonconscious emotional stimuli have indicated that subjects can be unaware of their own emotional responses [11, 46].…”
Section: Discussionmentioning
confidence: 99%
“…We performed an fMRI study using short video clips to present dynamic stimuli to participants (Prochnow et al 2013). For this purpose, video clips are better than static pictures because dynamic images induce higher activation in brain regions responsible for dealing with and generating aff ective content.…”
Section: Genotypingmentioning
confidence: 99%
“…Also in this context of priming effects is the work of Prochnow et al (Prochnow et al, 2013), that combined behavioral and fMRI (functional Magnetic Resonance Imaging) studies, aiming at examining whether or not consciously accessible (subliminal) emotional facial expressions influence empathic judgments and which brain activations are related to it. Their experiment showed that subliminal emotional facial expressions of 40 ms duration affect the judgments of the subsequent neutral facial expressions.…”
Section: Related Workmentioning
confidence: 99%